Estimated verbal IQ and the odds of problem gambling: a population-based study. Issue 8 (June 2014) - Rai, D.; Hall, W.; Bebbington, P.; Skapinakis, P.; Hassiotis, A.; Weich, S.; Meltzer, H.; Moran, P.; Brugha, T.; Strydom, A.; Farrell, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background The neurocognitive deficits and other correlates of problem gambling are also observable in individuals with lower cognitive abilities, suggesting that a low IQ may be a determinant of problem gambling. There has been very little research into this possibility. This study aimed to investigate the characteristics associated with problem gambling in a large population-based study in England, with a particular focus on IQ. Method The Adult Psychiatric Morbidity Survey (APMS) 2007 comprised detailed interviews with 7403 individuals living in private households in England. Problem gambling was ascertained using a questionnaire based on DSM-IV criteria. Verbal IQ was estimated using the National Adult Reading Test (NART). Confounders included socio-economic and demographic factors, common mental disorders, impulsivity, smoking, and hazardous drug and alcohol use. Results More than two-thirds of the population reported engaging in some form of gambling in the previous year, but problem gambling was rare [prevalence 0.7%, 95% confidence interval (CI) 0.5–1.0]. The odds of problem gambling doubled with each standard deviation drop in estimated verbal IQ [adjusted odds ratio (OR) 2.1, 95% CI 1.3–3.4, p = 0.003], after adjusting for other characteristics associated with problem gambling including age, sex, socio-economic factors, drug and alcohol dependence, smoking, impulsivity and common mental disorders. There was no strong relationship observed between IQ and non-problem gambling. Conclusions People with lower IQs may be at a higher risk of problem gambling. Further work is required to replicate and study the mechanisms behind these findings, and may aid the understanding of problem gambling and inform preventative measures and interventions.